The impact of non-Government organizations towards democratization and development The case of Runggiyan Social Development Foundation, Inc. - Monsanto, Cleto Jr. E. (Tacloban City Cleto E. Monsanto, Jr., 2009)
Runggiyan Social Development Foundation, Inc., one of the leading non-governmental organizations in Eastern Visayas is continuing its service of providing sustainable community development, empower women, youth and children through sustainable reproductive health, entrepreneurship development and alternative basic education. To comprehend NGOs like the Runggiyan Social Development Foundation whether they contribute to development and democratization, I intend to study the role of Runggiyan Social Development Foundation in its targeted community. In this regard, my objectives to this study is: (1) to identify how the RSDFI promotes community development towards its chosen community, (2) how to ascertain how the RSDFI promote political representation and participation to its chosen communities, and (4) how the organization responds to issue based situations occurring it its chosen locale. During the interview, I gathered some information about the organization's projects and programs such as the income livelihood projects in Barangay Barugo and Barangay Bukid through Roscas de Barugo production as well as Native Chicken Raising, theEnhancing Educational/ Entrepreneurial Access for School-Age Children and Youth or EASY program, the organization's contribution in creating gender equality and protection of women's rights through Bantay Panimalay in Tacloban and Leyte, the Bantay Banay network program, and the Empowering Girls Project. Runggiyan Social Development Foundation has created a great impact towards development and democratization. In its numbers of people and househols it helped,Runggiyan has gained a strong impression for the people of Region VIII. The foundation provided better programs and projects that have helped support and assist many people of Eastern Visayas and created an Avenue for citizen participation.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science